Cassava Root Chips as an Alternative Energy Feed Ingredient in Broiler Ration - Tesfaye , Etalem; Animut, Getachew; Urge, Mengistu; Dessie, Tadelle (International Journal of Poultry Science, 2013)
A total of 300 day-old Hubbard Classic broiler chicks with initial body weight (BW) of 43.6±1.33 (mean±SD) were randomly and equally distributed into 15 pens, representing five feeding treatments with three replication per treatment to evaluate the performance of chicks fed varying dietary levels of cassava root chips (CRC) replacing corn grain (CG). Treatments were replacement of CG with CRC at 0 (T1), 25 (T2), 50 (T3), 75 (T4) and 100% (T5) levels. Isocaloric and isonitrogenous starter and finisher rations were used. Four birds 2 from each sex were randomly taken from each replication and slaughtered for carcass evaluation at the end of the study. The metabolizable energy content of CRC and CG were 3852 and 3753 kcal/kg dry matter (DM), respectively. Daily DM intake during the entire experimental period ranged 61 to 67 g/bird and was greater (P0.05) among treatments. Replacement of CRC for CG at higher levels (75 and 100%) lowered (P